Air Pollution Assessment in the Main Roads of Surabaya-Indonesia During Post Covid-19 - Ida MUNFARIDA; Vera ARIDA (International Journal of Environmental, Sustainability, and Social Science, 2023)
An increase in population in Surabaya City may have an impact on the activities of industrial, trade and service centres. One of the most important supporting facilities is the transportation sector. The use of fuel in transportation is the main cause of the impact on air quality. This study aims to evaluate the concentration of carbon monoxide on main roads in Surabaya City and to analyse the effect of vehicles on carbon monoxide on the main roads in the city of Surabaya on covid-19 transition. The research was conducted in the field by directly measuring the concentration of carbon monoxide and the number of vehicles on three main roads in Surabaya. The results of carbon monoxide measurements and the number of vehicles were analysed using linear regression. This research reveals that in general, the carbon monoxide concentration has exceeded the air quality standard based on Government Regulation no. 22 of 2021. This result indicates that many people have travelled for various activities in the city after the covid-19 outbreak. In addition, based on the results of the linear regression test, it is known that there is a significant effect of the number of vehicles on the carbon monoxide concentration (?<0.05).